Impact of Persuasive Instagram Posts on Gen Z Mangrove Ecosystem Concern - Paundra Hanutama; Thomas Stefanus Kaihatu; Timotius Febry Christian; Muh. Ilham Kholid (Jurnal Penelitian Pendidikan IPA, 2026)
Mangroves are a type of tree that play an important role in maintaining the balance of the coastal ecosystem. The decline in mangrove area and function due to urbanization pressures requires the active involvement of the younger generation in conservation efforts, particularly through digital media. Mangrove conservation activities necessitate the involvement and knowledge of Generation Z. Communication is an aspect that can impact knowledge of mangrove conservation. However, communication delivered in the form of visual images, audio, or graphics that explain the negative impacts makes people feel compelled to participate or vice versa. The purpose of this study is to examine the effectiveness of persuasion of positive and negative information posted on the Jakarta Mangrove Community's Instagram social media account on Generation Z's understanding of the mangrove forest ecosystem in Jakarta. The method employed is a quantitative survey with data collection procedures utilizing a questionnaire. An examination of survey data for Generation Z reveals a good association between the type of Instagram social media material and environmental awareness of the mangrove ecosystem. Whereas the substance of Instagram posts providing positively or negatively packaged critical information on mangrove forests and their environmental impact has a large overall influence on Generation Z's understanding of the need for mangrove forest ecosystems. Using Instagram as a social media platform to raise awareness among Generation Z communities about the efforts that can be made to conserve mangrove forest ecosystems is an effective technique.